If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + -2 = 3x + 4 Reorder the terms: -2 + Y = 3x + 4 Reorder the terms: -2 + Y = 4 + 3x Solving -2 + Y = 4 + 3x Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + Y = 4 + 2 + 3x Combine like terms: -2 + 2 = 0 0 + Y = 4 + 2 + 3x Y = 4 + 2 + 3x Combine like terms: 4 + 2 = 6 Y = 6 + 3x Simplifying Y = 6 + 3x
| 8.5x^3-79.6875x-164.171=0 | | 8y-16+3y+9=90 | | 3=2a/3=15 | | 5x-6-3x+2=10 | | 2=3-x/34 | | 9(j-9)= | | lne^2x=8 | | f(x)=2x^2+14x+22 | | 6x-28=6x-4 | | 42-4u=3u | | x^2-6x-25/16 | | 6(2x-4)=8(x+2) | | 4(x-4)-1=-5(-5x+5)-7x | | (10x^3-18x^2)/2x^2 | | 3+2ab-4ac+6bc= | | 2(x-2)+2x=4 | | (X-19)+17=63 | | -24b=-48 | | 1p^2+2p-24=0 | | 7(b+10)= | | -2/3n-4=5 | | (x+16)(x-18)=180 | | 4x+10=3x-4 | | -2(u+1)=-2(9u-7)+4u | | 3(-2+7x)=-27 | | 1250w^10z^5/20w^2z^2 | | 2z+7=3z-11 | | 1-5x=6x-10 | | 3(u+2)+2u=7(u-1)+1 | | 3x+2(3x+5)-4(3x+4)+3(3x+2)+8=0 | | (8x+8)+(-9x+9)= | | x^2+8y+6x=y^2-18 |